The Autonomous Eye: How AI in Retinal Imaging is Revolutionizing Early Detection of Diabetic Retinopathy - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The global burden of Diabetic Retinopathy DR, a leading cause of preventable blindness among working-age adults, presents a significant public health challen...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning